2003
DOI: 10.1074/jbc.m306441200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Murine Interleukin-12 p40 Promoter by Functional Interactions between NFAT and ICSBP

Abstract: Interleukin (IL)-12 is a heterodimeric cytokine that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 49 publications
7
87
0
Order By: Relevance
“…1, and TNF-␣ expression was determined by RT-PCR. (63). In this study we demonstrate that MSP inhibits IL-12 production primarily by repressing the expression of the p40 subunit.…”
Section: Discussionmentioning
confidence: 51%
“…1, and TNF-␣ expression was determined by RT-PCR. (63). In this study we demonstrate that MSP inhibits IL-12 production primarily by repressing the expression of the p40 subunit.…”
Section: Discussionmentioning
confidence: 51%
“…The molecular mechanism for this enhancement has been controversial but recently a novel complex between NFAT and IFN regulatory factor (IRF)-8 was shown to bind to the IL-12p40 promoter following LPS plus IFN-␥ macrophage activation (36). IL-10 is known to inhibit IL-12 production by inhibiting IL-12p40 gene expression at the level of transcription (29), and Zhu et al (36) demonstrated that IL-10 interfered with the formation of the IRF-8/NFAT complex. Recent data have demonstrated that pretreatment of BMDCs with IFN-␥ resulted in increased levels of expression of TLR9 (37).…”
Section: Discussionmentioning
confidence: 99%
“…IRF-8 Ϫ/Ϫ macrophages display selective impairment of IL-12 p40 expression but not other cytokines, such as IL-1, IL-6, and TNF-␣ (32,33). The promoter of the IL-12 p40 gene contains an Ets site as well as a composite IRF-8-nuclear factor of activated T cells DNA-binding element, both of which play an important role for the expression of IL-12 p40 (34,35). In contrast, IRF-4 Ϫ/Ϫ macrophages produce excessive cytokines, including IL-6, TNF-␣, and IL-10, in response to LPS, suggesting that the regulation of cytokine production by IRF-4 is distinct from that by IRF-8.…”
Section: Discussionmentioning
confidence: 99%